Mesenchymal Stem Cell Therapy in the Treatment of Acute and Chronic Graft Versus Host Disease - Kebriaei, Partow; Robinson, Simon (Frontiers in Oncology, 2011)
Mesenchymal stem cells (MSC) are a cellular component of the supportive microenvironment (stroma) found in the bone marrow, umbilical cord, placenta and adipose tissues. In addition to providing cellular and extracellular cues to support the proliferation and differentiation of cells that comprise functional tissues, MSC also contribute to tissue repair and have immunomodulatory properties. Their ability to modulate immunologic reactions while themselves not provoking immunologic responses from alloreactive T-lymphocytes and/or other effector cells, make MSC a potentially ideal therapeutic agent with which to treat graft versus host disease (GvHD) following hematopoietic transplantation. Despite in vitro experiments confirming that MSC suppress mixed lymphocyte reactions (MLR) and in vivo evidence from mouse models that show evidence that MSC can ameliorate GvHD, clinical trials to date using MSC to treat GvHD have shown mixed results. Whether this is a consequence of suboptimal timing and dose of administered MSC remains to be clarified. It is clear that immunomodulatory potential of MSC as a cellular therapy for GvHD remains to be realized in the clinic.